Electronic structure of cubic ScF3 from first-principles calculations - Bocharov, D.; Žguns, P.; Piskunov, S.; Kuzmin, A.; Purans, J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
The ground state properties of cubic scandium trifluoride (ScF3) perovskite were studied using first-principles calculations. The electronic structure of ScF3 was determined by linear combination of atomic orbital (LCAO) and plane wave projector augmented-wave (PAW) methods using modified hybrid exchange-correlation functionals within the density functional theory (DFT). The comprehensive comparison of the results obtained by two methods is presented. Both methods allowed us to reproduce the lattice constant found experimentally in ScF3 at low temperatures and to predict its electronic structure in good agreement with known experimental valence-band photoelectron and F 1s x-ray absorption spectra.